Group B Streptococcus vaginal colonisation throughout pregnancy is associated with decreased Lactobacillus crispatus and increased Lactobacillus iners abundance in the vaginal microbial community - Maidment, Toby I.; Pelzer, Elise S.; Borg, Danielle J.; Cheung, Eddie; Begun, Jake; Nitert, Marloes Dekker; Rae, Kym M.; Clifton, Vicki L.; Carey, Alison J. (Frontiers in Cellular and Infection Microbiology, 2024)
Group B Streptococcus (GBS) asymptomatically colonises the vagina of up to 40% of pregnant women and can transmit to neonates during birth, causing neonatal pneumonia, sepsis, meningitis, and significant mortality. Vaginal GBS colonisation can be attributed to a range of host and bacterial factors, which may include the composition of the vaginal microbial community. There are few studies that have examined the vaginal community composition in relation to GBS colonisation throughout pregnancy. Here, we performed 16S rRNA sequencing (V3-V4) on vaginal swabs from women at 24- and 36-weeks’ gestation, who were GBS culture-negative or GBS culture-positive at either 24 weeks or 36 weeks’ gestation or at both timepoints. Vaginal swabs from 93 women were analysed; 46 women were culture-negative, 11 women GBS culture-positive at 24 weeks only, 21 women GBS culture-positive at 36 weeks only and 15 women GBS culture-positive at both timepoints on Brilliance GBS agar. V3-V4 16S rRNA gene amplicon sequencing demonstrated that in women that were GBS culture-positive at 36 weeks gestation only, G. vaginalis was significantly more abundant at 24-weeks’ gestation despite a lack of significant changes in community richness between the 24- and 36-week samples. The vaginal microbial communities of women persistently colonised with GBS, had a significantly higher abundance of Lactobacillus iners, compared to other groups where L. crispatus, L. gasseri or L. jensenii were dominant. We have characterised the vaginal microbial community composition during pregnancy in relation to GBS colonisation status, in a longitudinal study for the first time. The most interesting finding was that in women that were persistently colonised with GBS throughout pregnancy, there was a significant increase in L. iners and significant reduction in L. crispatus abundance. Given the lack of detail of the role that the vaginal microbial community plays in GBS colonisation in the literature, it is imperative that the relationship between L. iners and GBS in this unique environmental niche is further investigated.